Analysis of the Energy Complex Member of the EАEU Countries and the Formation of Groups-Technologies of its Digitalization - M. I. Rusetskaya; T. F. Mancerova; E. P. Korsak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Due to the increasing internationalization of the member countries of the Eurasian Economic Union (EAEU), it is planned to create a common energy market and an electric energy market. To ensure the reliable functioning of the energy systems of individual states of the Union and their common energy market, it is necessary to increase energy efficiency and reduce costs at each stage of production, transmission, distribution and sale of electricity by optimizing processes in the industry through the introduction of digital technologies. The purpose of this work is to analyze the electric power complexes of the EAEU member states and to consider groups of digitalization technologies of industries in the context of the electric power industry, to form an algorithm for creating a classification of digitalization technologies of the electric power industry and on the basis of the latter to create the classification itself. The article provides an overview of the dynamics of the main economic indicators of the Union countries and the main indicators of their electric power industries, examines the structure of electricity production, energy portfolio, average electricity prices, total electricity consumption by sector. The import-export potential and the level of electricity losses in the networks have been analyzed. The interpretation of digital technologies of the electric power complex in the context of existing groups-digitalization technologies was made, the components of the interconnection of digital technologies were identified; the classification of the above components by production stages has been developed. Recommendations on the further use of the classification for the formation of an indicative system for assessing the level of digitalization of the electric power complex are put forward. It is concluded that digitalization of the electric power system on the technical side increases the energy security of the state and the competitiveness of the energy system on the world market, and on the economic side it helps to reduce costs at all stages of the entire technological cycle.